Proses Pelaksanaan Pembelajaran Dalam Meningkatkan Kualitas Pendidikan Di Era New Normal - Ni Made Anggreni (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2021)
The implementation of learning in the new normal era is a concern for all parties because learning is considered not to be implemented optimally. The quality of education is also questionable because of the lack of ready education facilities online or in the network (online). Even parents who experience a lot of job loss feel burdened with children who have to study from home because they need special assistance for children who are less able to be independent. The government has also tried to issue assistance in the form of quotas, and schools are given policies to manage BOS funds to be used to prepare health protocol facilities. Given the increasing number of positive Covid-19, lessons that are carried out offline cannot be implemented. This is where the role of parents is very much needed to help the education of their sons and daughters for the continuation of a smooth educational process in the midst of this pandemic. The role of a teacher cannot be separated from being a learning facilitator and is added to monitor the learning process that is carried out offline. With this collaboration, it is hoped that parents and teachers will make contact via online to support learning in the new normal era.